The Policy Development Process and the Agenda for Effective Institutions: The Philippines - Gilberto M. Llanto (Philippine Institute for Development Studies (PIDS), 2007)
A developing economy such as the Philippines has to create an enabling environment for economic growth and development. But how does one nudge forward the creation of such an environment? This paper departs from the usual discourse on the need for effective implementing institutions. Instead, it discusses the critical role played by "supporting" institutions such as independent review institutions or commissions and coordinating institutions in moving forward the policy development process. Those supporting institutions can provide policymakers and the general public an objective assessment of the results of development efforts, performance reviews, and recommendations on future pathways for reform and development. The paper provides concrete examples of Philippine institutions that may be tasked to do such objective ex ante or ex post reviews.
Keywords: 330; policy development process; enabling environment; support institutions; ex ante and ex post reviews; output framework; policy outcomes; Entwicklungspolitik; Institutionelle Infrastruktur; Philippinen